2020
DOI: 10.1080/21870764.2020.1718859
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum slurry evaluation method for the prediction of BaTiO3 green sheet density

Abstract: In this study, the particle dispersion state in a dense BaTiO 3 slurry containing a dispersant and binder was assessed by various slurry evaluations such as particle size distribution measurement by laser diffraction, viscosity measurement, dynamic viscoelasticity measurement, and hydrostatic pressure measurement, which is a novel slurry evaluation technique developed by our group. Then, the relationship between the slurry evaluation results and the packing fraction of green sheets fabricated from these slurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These authors reported that this was caused by insufficient inter‐particle repulsion forces, the interaction between the dispersant and the binder, and the degradation of the dispersant by the dispersing process. In our past studies, which examined pH‐controlled alumina slurry 24,25 and slurry containing PCA and PVA, 32,39 the change of particle dispersion state in the slurry during sedimentation had already been confirmed; so it was expected that this phenomena would also occur in the current study. Consequently, a verification test to confirm it was conducted, and the changes of particle dispersion state were demonstrated, as shown in Figure .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…These authors reported that this was caused by insufficient inter‐particle repulsion forces, the interaction between the dispersant and the binder, and the degradation of the dispersant by the dispersing process. In our past studies, which examined pH‐controlled alumina slurry 24,25 and slurry containing PCA and PVA, 32,39 the change of particle dispersion state in the slurry during sedimentation had already been confirmed; so it was expected that this phenomena would also occur in the current study. Consequently, a verification test to confirm it was conducted, and the changes of particle dispersion state were demonstrated, as shown in Figure .…”
Section: Discussionmentioning
confidence: 60%
“…Generally, a slurry whose particles are well dispersed has low apparent/relative viscosity and is assumed to form a dense sediment; however, our study demonstrates different results. Some findings reported in previous studies indicated that the apparent viscosity of the just‐prepared slurry did not completely correlate with the packing fraction of the sediment, or the particle dispersion state changed over time 24,25,32,37–39 . These authors reported that this was caused by insufficient inter‐particle repulsion forces, the interaction between the dispersant and the binder, and the degradation of the dispersant by the dispersing process.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ceramic slurries are of great importance in applications ranging from ceramic manufacturing processes to ceramic shaping processes such as slip-casting, tapecasting, and spray-drying. [1][2][3] In the ceramic manufacturing process, the dispersion characteristics of the powder affect the physical and sintering properties of the slurry. Here, dispersion refers to a state in which solid particles are homogeneous and form a stable suspension in a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Enabling the creation of a computational connection between the rheological characteristic of the slurry and the dispersion and aggregation states of the particles would be useful, because slurry is often practically evaluated by measuring viscosity, which is fast and easy to perform. [16][17][18][19][20][21][22][23] The adsorption of dispersant for various particles was also studied by molecular dynamics (MD) simulations and density functional theory (DFT) calculations because the behavior of dispersant close to the solid surface plays a major role in predicting the rheological characteristic of a slurry. [24][25][26] Numerous experiments and theoretical simulations have been performed for the optimization of slurry preparation, but a molecular-level exploration of the microstructurerheology relationship is still lacking.…”
Section: Introductionmentioning
confidence: 99%